UPPER AGE BOUNDARY OF THE ACCRETION OF TERRANES IN THE NORTHWESTERN PART OF THE EASTERN SEGMENT OF THE CENTRAL ASIAN FOLDBELT - Reznitsky L.Z.; Barash I.G.; Belichenko V.G.; Kotov A.B.; Sal'Nikova E.B.; Glebovitsky V.A.; Kovach V.P.; Yakovleva S.Z.; Fedoseenko A.M. (My University, 2007)
Different concepts have been proposed for the sequence and character of the accretionary and collisional processes during formation of mosaic structures in the northwestern part of the eastern segment of the Central Asian Foldbelt (CAFB) framing the Siberian Craton. According to one of the latest models, these events started with the formation of the accretionary Caledonian superterrane, which was later softly amalgamated to the craton along the strike-slip boundary. The large-scale accretion of different terranes and their collision with the craton are traditionally considered as nearly simultaneous processes. However, it is suggested that individual terranes were preliminarily amalgamated or accreted into large tectonic units (composite terranes). The upper age boundary of the accretionary–collisional processes is determined with great uncertainty (450–490 Ma).